The Effect of Interest Rates, Non-Performing Loans (NPL), and Company Size on The Financial Performance (ROA) of PT Bank Rakyat Indonesia (Persero) Tbk for The Period 2014-2024 - Dominika Dora Soge; Iman Lubis (Indonesian Economic Review, 2026)
This study was conducted to determine the effect of interest rates, non-performing loans (NPLs), and company size on the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk during the period 2014–2024. In this study, financial performance was proxied using return on assets (ROA) as an indicator of a company's ability to utilize its assets to generate profits. The method used is a quantitative approach with an associative research type. The research data consisted of secondary data sourced from the annual financial reports of PT Bank Rakyat Indonesia (Persero) Tbk, Bank Indonesia publications, and various other official sources relevant to the observation period. Data analysis was performed through descriptive statistics, classical assumption testing, and multiple linear regression to assess the effect of independent variables on dependent variables, both partially and simultaneously. This study is expected to provide empirical evidence on the factors that influence banking financial performance, particularly those related to changes in interest rates, credit risk levels, and company size. In addition, the results of this study are expected to be taken into consideration by management in strategic decision-making and to serve as a reference for investors, regulators, and future researchers in the field of financial management and banking.